Exploration of the Relationship between Optimism, Resilience, and Psychological Well-Being in Guidance and Counseling Students - Harum, Akhmad Harum; Suciani Latif,; Muzayyinah Al Uzrah, (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2025)
The purpose of this study was to examine the relations of optimism, resilience, and psychological well-being in guidance and counseling students. The method used in this research is descriptive quantitative. Data were collected through questionnaires, using 3 scales, namely the optimism scale (Revised Life Orientation Test/LOT-R), resilience scale (Connor-Davidson Resilience Scale/CD-RISC), and psychological well-being scale (Psychological well-being Ryff's Scale). A total of 246 guidance and counseling students participated in this study. The research data were analyzed using descriptive analysis techniques and multiple regression analysis. The results of this study indicate that there is a significant relationship between optimism and resilience variables on students' psychological well-being. The optimism variable has a positive influence on psychological well-being, while the resilience variable has an opposite (negative) influence on the psychological well-being of guidance and counseling students. Thus, it can be concluded that although guidance and counseling students have a high level of resilience, students may also experience greater stress, pressure, or demands so that resilience negatively affects the psychological well-being felt by students. In addition, students who have a high sense of optimism will tend to improve psychological well-being.